Expansive and collapsing behaviour of volume change soils - De Sousa Vinagre, Tiberio J V; De Sousa Vinagre, Tiberio J V (Department of Civil Engineering, 2017)
This thesis is designed to achieve three goals: Goal One - to introduce the reader to soils exhibiting expansive and/or collapsing behaviour; Goal Two - to provide an in depth understanding of aspects of this behaviour, obtained from an extensive study of these soil types; and, Goal Three - to serve as a reference for future research work (a recommendation for further research proposed in Chapter Ten of this thesis). The thesis is divided in two main parts. In the first part representative soil types were selected on the basis of their properties and expected engineering behaviour. The soil structure and clay minerals were also studied in part one of this thesis. The second part of the thesis deals with aspects of expansive and collapsing behaviour of soils. Chapter three provides the introduction to the subsequent chapters on expansive and collapsing behaviour of volume change soils.